The Female Dimension of the Board of Directors and its Impact on Firm Value: A Narrative Review - Granata, Giuseppe; Turchetta, Anna; Gigli, Sara; Cennamo, Antonio (European Scientific Journal, ESJ, 2025)
This paper aims to study the existing relationship between the female dimension of the board of directors and its impact on firm value. It is essential to stop and focus on why it is crucial to create value inside companies. The board of directors is the centre where major business decisions are made. The future success or failure of the company depends on the decisions that directors make today. The idea of the future companies comes from the board of directors. From here, we understand the importance of profoundly reading the mechanisms that govern this organization. If we analyse the etymological sense of the term “value,” we consider everything worthy of being considered: economic benefits, but not only. In recent years, corporate culture has been a discriminating factor when the economic crisis has led companies to exercise resilience actions. The COVID-19 pandemic and the international unrest then questioned how to do business. The market scenarios in which companies operate have changed. One element that made the difference was the mental flexibility of administrators. During these years, the company culture has made a difference. We provided a critical and narrative review of the most significant academic research papers and texts dedicated to studying the culture of women’s enterprises. The database that was used for the search is Scopus. The study was conducted to offer a new key to reading these phenomena.